Relationship between hypothyroidism and the incidence of gestational diabetes: A meta-analysis - Li-Li Gong; He Liu; Li-Hong Liu (Elsevier, 2016)
Objectives: Hypothyroidism disorders and gestational diabetes are among the most common endocrinopathies during pregnancy. We conducted a meta-analysis to investigate whether hypothyroidism in pregnancy is associated with gestational diabetes risk. Materials and methods: Published literature from PubMed and EMBASE were searched for eligible publications. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a fixed- or random-effects model. Results: Seven articles described the relationship between hypothyroidism and risk of gestational diabetes. This meta-analysis revealed that overt hypothyroidism was associated with an increased risk of gestational diabetes (OR 1.892, 95% CI 1.679-2.132, p < 0.001). The relative risk of gestational diabetes was also increased in subclinical hypothyroidism, with the OR of 1.558 (95% CI 1.292-1.877, p < 0.001). There was no evidence of significant association between hypothyroxinemia and risk of gestational diabetes (OR 1.394, 95% CI 0.753-2.580, p = 0.291). The OR for all of the hypothyroidism was 1.749 (95% CI 1.586-1.928, p < 0.001), and an association was found. Conclusion: Results of this meta-analysis indicate that hypothyroidism may be a risk factor for gestational diabetes.